A comparative evaluation of the dentinal microcracks formed and propagated during the removal of gutta-percha using hand and three rotary retreatment file systems: A micro-computed tomography study - Srivastava Sanjeev; Rita Gupta; Dubey Sandeep; Tewari Tanu; Shukla Namita; Singh Arohan (Wolters Kluwer Medknow Publications, 2023)
Aim: This micro-computed tomography (micro-CT) study aims to quantitatively analyze the dentinal microcracks formed and propagated after endodontic retreatment using different file systems. Methods: Forty extracted mandibular premolars were selected. Biomechanical preparation was done using ProTaper Next rotary files followed by obturation using lateral compaction technique. All specimens were randomly divided into four groups (n = 10) and scanned under 1172; Micro-CT (Skyscan Bruker, Kontich, Belgium). After scanning, the first group was retreated using Hedstrom (H) files (Dentsply Maillefer, Ballaigues, Switzerland), the second group with Gutta Percha Remover (GPR) files (Mani Inc., Japan), the third group with Endostar RE Re Endo Rotary system (RE Endo files) (Endostar RE, Poland), and fourth group with ProTaper Universal Retreatment (PTUR) files (Dentsply Maillefer, Ballaigues, Switzerland). A micro-CT scan was repeated of each sample to observe the newly formed and propagated microcracks. The micro-CT scans before and post retreatment were then evaluated using CT-analyzer software. Data were compared using the Chi-square test. Results: New microcracks formed post retreatment were maximum in the RE Endo group followed by the PTUR group, GPR group, and least in the H file group. Propagation of existing microcracks after retreatment was maximum in the RE Endo group followed by nearly similar in both the GPR group and PTUR group and least in the H file group. On comparing the frequency distribution of the newly formed and propagated microcracks, the Chi-square test showed similar distribution among all four groups, which was found statistically insignificant (P > 0.05). Conclusion: GPR rotary instrument group created the least new microcracks among tested retreatment rotary files. However, the propagation of microcracks was found comparable with the PTUR files.